Representasi Kesetaraan Gender Axe Pocket Parfume Versi ‘Dijemput Si Cantik: Kajian Semiotika Barthes - Rahmah, Rizka Fatchur; Wibowo, Arif Ardy (Acintya, 2023)
As a mass media with a mirror function, advertising can reflect social reality formed from the media’s construction. Gender issues shaped by advertisements that are aired repeatedly will enter into the mindset of the people. In 2020, AX Indonesia published an ad for its newest product, the AX Pocket Perfume version of ‘Dijemput Si Cantik,’ which shows a female online motorcycle taxi driver picking up male customers. In  contrast  to  the  representation  of  women  in  previous  advertisements,  which  always  showed  women doing household activities. This study aims to determine the depiction of gender equality in the ad for the AX Pocket Perfume version of ‘Dijemput Si Cantik.’ A qualitative approach is used with descriptive explanations. The analysis theory used is Roland Barthes’ semiotic analysis. The data collection technique in this study was to use the documentation method, namely to collect data from books, e-books, journals, and information from official sites on the internet as well as audio and visual materials, advertisements for the AXE Pocket Perfume version of ‘Dijemput Si Cantik.’ The results indicate that the depiction of gender equality in the ad for the AXE Pocket Parfume version of ‘picked up by the beauty’ is incomplete. This advertisement presents gender equality but contains gender bias.Keywords: advertisement, gender equality, representation, semiotic